2020
DOI: 10.34172/ijhpm.2020.135
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Governance: Developing a Novel Metric for Assessing Whether Policy Environments are Conducive for the Development and Implementation of Nutrition Interventions in Nepal

Abstract: Background: The Nutrition Governance Index (NGI) defines a first standardized approach to quantifying the ‘quality of governance’ in relation to national plans of action to accelerate improvements in nutrition. It was created in response to growing demand for evidence-based measures that reveal opportunities and challenges as nutrition-related policies on paper are translated into outcomes on the ground. Numerous past efforts to measure ‘governance,’ most notably World Health Organization’s (WHO’s) NGI and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…With respect to the policy and legislation theme, this review revealed how supportive political environments and nutrition-specific guidelines ease the implementation process by removing logistical barriers and increasing the motivation or commitment of personnel. This idea was echoed by a recent study conducted by Namirembe et al (2020), where researchers stated that individual nutrition programs are more sustainable and cost effective when they are supported by structures and policies that fit with program goals. Interventions do not exist in a vacuum; thus, factors such as political commitment to carrying out nutrition-relevant policies are part of the requirement for achieving desirable nutrition outcomes (Namirembe et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the policy and legislation theme, this review revealed how supportive political environments and nutrition-specific guidelines ease the implementation process by removing logistical barriers and increasing the motivation or commitment of personnel. This idea was echoed by a recent study conducted by Namirembe et al (2020), where researchers stated that individual nutrition programs are more sustainable and cost effective when they are supported by structures and policies that fit with program goals. Interventions do not exist in a vacuum; thus, factors such as political commitment to carrying out nutrition-relevant policies are part of the requirement for achieving desirable nutrition outcomes (Namirembe et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This idea was echoed by a recent study conducted by Namirembe et al (2020), where researchers stated that individual nutrition programs are more sustainable and cost effective when they are supported by structures and policies that fit with program goals. Interventions do not exist in a vacuum; thus, factors such as political commitment to carrying out nutrition-relevant policies are part of the requirement for achieving desirable nutrition outcomes (Namirembe et al 2020). For example, South Africa's integrated nutrition strategy, later known as the Integrated Nutrition Program (INP), aimed to incorporate nutritional promotion at various policy levels (Labadarios et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The five recent and widely cited indices to assess MNG are as follows: (i) the WHO Nutrition Governance Index (WHO's NGI) which ranks governments on their 'commitment' (willingness to act) and 'capacity' (readiness to act) to improve nutrition, (ii) the Hunger and Nutrition Commitment Index (HANCI) which ranks governments on their political commitment to addressing undernutrition while seeking to measure what governments achieve and where they fail (65) , (iii) the Political Commitment (for Nutrition) Rapid Assessment Tool which measures a country's level of political commitment and identifies opportunities to advance food and nutrition on governmental agendas (66) , and (iv) MNG framework by World Bank which aims at qualitatively assessing enablers and barriers of MNG at the country level (45) . The recently developed NGI by Tufts University is the first standardised approach to quantifying the MNG in relation to national plans of action to accelerate improvements in nutrition (64) . In addition to these global frameworks and tools, individual countries have also developed their metrics to assess MNG.…”
Section: Metrics Used To Assess Multisectoral Nutrition Governance An...mentioning
confidence: 99%
“…Challenges in achieving multisectoral nutrition governance Several challenges that developing countries are encountering as they strive to establish effective MNG have been identified. These challenges can be attributed to various factors, including inadequate leadership and guidance, limited resources, weak institutional capacity, fragmented coordination mechanisms, and competing priorities among others (18,25,37,45,48,64) . Challenges specific to Kenya are given in the following sections.…”
Section: Multisectoral Nutrition Governance Context In Kenyamentioning
confidence: 99%
“…Adding nutrition-related objectives to official policies or strategies is not sufficient as even attempts at measuring results and decisions in nutrition governance can be problematic, for instance how to measure (e.g. what indicators to include) governments' 'commitment' or 'capacity' in addressing nutrition-related questions (Namirembe et al 2021(Namirembe et al , 2022. To tackle these complexities and make headways in its endevours, a nutrition-sensitive governance of fisheries requires breaking outside of the technical arena of 'implementation' and develop links between theory and practice, values and actions, and between different forms of knowledge, requiring changes in the current ways fisheries are thought of and managed.…”
Section: Governancementioning
confidence: 99%